Kinetics and mechanism of the hydrogen-evolution reaction on mercury in HCl-dimethylsulphoxide solutions - Posadas, Dionisio (1973)
Rapid galvanostatic and potentiostatic stationary E/I curves, E/time characteristics at current interruption and electrode capacitance measurements were made to investigate hydrogen-ion discharge on mercury in HCl-DMSO solutions, with and without the addition of LiCl as supporting electrolyte. Kinetic parameters and their temperature and concentration dependences are discussed in terms of the initial electron-trnsfer reaction as rate-determining.